CLINICAL-FUNCTIONAL ANALYSIS OF TRIGEMINAL NEURALGIA MANIFESTATIONS IN CASE OF ITS LONG DURATION - Рибалов, О.В.; Іваницька, О.С.; Іваницький, І.О.; О. П. Буханченко В. О. Ратанчук; Ratanchuk V. O. (World of Medicine and Biology, 2014)
The article deals with the results of a complex examination of patients with trigeminal neuralgia based on clinical analysis of the functioning of the peripheral nerve, on evaluation of a stomatological and psycho-emotional status, as well as the study of electrophysiological parameters of proper masticatory muscles. Obtained data revealed several features of clinical-functional display of trigeminal neuralgia in case of its long duration. In future, this will make it possible to develop treatments that can adequately influence the main elements of the pathological process.